1991
DOI: 10.1007/bf01955524
|View full text |Cite
|
Sign up to set email alerts
|

Cystic fibrosis and Helicobacter pylori gastritis, megaloblastic anaemia, subnormal mentality and minor anomalies in two siblings: a new syndrome?

Abstract: Two siblings of consanguineous Arab parents were found to have cystic fibrosis and gastritis associated with Helicobacter pylori, folate deficiency megaloblastic anaemia, subnormal mentality and minor anomalies. The association of H. pylori and megaloblastic anaemia has not been described in patients with cystic fibrosis. H. pylori infection and gastritis is probably more common in patients with cystic fibrosis than appreciated. We believe that the constellation of features in the two sibs represent a possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Several case reports and a few larger‐scale studies on H. pylori in persons with ID have been published. Lubani et al (1991) described two siblings from Kuwait with developmental disability, cystic fibrosis and H. pylori gastritis. Mauk (1995) described a 6‐year‐old boy from Philadelphia with severe ID, rumination and H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports and a few larger‐scale studies on H. pylori in persons with ID have been published. Lubani et al (1991) described two siblings from Kuwait with developmental disability, cystic fibrosis and H. pylori gastritis. Mauk (1995) described a 6‐year‐old boy from Philadelphia with severe ID, rumination and H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…Lubani et al [11] from Kuwait described two siblings with developmental disability, cystic fibrosis and Helicobacter gastritis; Mauk [12] from Philadelphia described a 6-year-old boy with severe mental retardation, rumination, and several other behavioral disorders. Helicobacter infection was found on examination, treated and clinical improvement found as decreased frequency of rumination and gain of weight.…”
Section: Discussionmentioning
confidence: 99%
“…Growth failure and malnutrition are common in children with cerebral palsy, particularly in those with spastic quadriplegia, of which 85% report feeding problems [30,31]. In addition, 20-30% of hemiplegic and diplegic cerebral palsy children are underweight for age [26,32]. There are multifactorial causes: insufficient food intake, feeding problems, increased nutrient losses from vomiting or diarrhea, and alterations in energy requirements in epileptic or metabolic syndromes where increased muscle tone or involuntary movements are seen.…”
Section: Helicobacter Infection and Gastric Neoplasiamentioning
confidence: 99%
“…Good number of studies have been published in persons with intellectual disability, however, large-scale scientific studies have not been published with a population case-control study [22,32,34]. Harris et al [35] (10) reported that hospital residents under 40 years of age had a 87% prevalence of HP compared with 24% for controls, whereas the overall prevalence for all ages was 87% for residents, and 43% for controls in hospital residents with severe learning disabilities.…”
Section: Helicobacter Infection and Gastric Neoplasiamentioning
confidence: 99%